2008
DOI: 10.1097/01.prs.0000293763.82790.aa
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Spine Injury in Association with Craniomaxillofacial Fractures

Abstract: The relationship between cervical spinal injuries and craniomaxillofacial trauma has been better defined as it relates to a regional trauma registry. The implications as related to the trauma assessment, diagnosis, and treatment of these injuries are reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(10 citation statements)
references
References 31 publications
(42 reference statements)
1
9
0
Order By: Relevance
“…Midface fractures propose an independent risk factor for cervical spine injuries [20]. In our cohort the incidence of cervical spine fractures in patients with midface fractures was 7.8% (16/204) which indicates similar relevant levels as previously reported by other teams (2.6% by Ardekian et al-9.7% by Mithani et al) [20][21][22][23][24][25]. Therefore, diagnostics and treatment of CMF and OT patients in trauma centers with a department for spinal surgery is strongly advised.…”
Section: Cervical Spine Injuries In Patients With Midface Fracturessupporting
confidence: 90%
“…Midface fractures propose an independent risk factor for cervical spine injuries [20]. In our cohort the incidence of cervical spine fractures in patients with midface fractures was 7.8% (16/204) which indicates similar relevant levels as previously reported by other teams (2.6% by Ardekian et al-9.7% by Mithani et al) [20][21][22][23][24][25]. Therefore, diagnostics and treatment of CMF and OT patients in trauma centers with a department for spinal surgery is strongly advised.…”
Section: Cervical Spine Injuries In Patients With Midface Fracturessupporting
confidence: 90%
“…Previous studies have estimated the complication rate of trauma patients admitted to the ICU to be 17.0- 31.2%, 16 , 17 whereas, others have found complication rates of 12.0-50.3% for traumatic facial fractures. 9 , 19 , 20 Studies have shown age, gender, traumatic CNS injury, chronic alcohol use, the type of intensive care unit, and number of operations to influence complication rates. 16 , 17 , 21 , 30 , 31…”
Section: Discussionmentioning
confidence: 99%
“…Although many studies have investigated the epidemiology of maxillofacial injures, most of them focus on a single type of concomitant injury like brain or cervical spine [911], have emphasized on concomitant injuries with a particular type of facial fracture [12, 13], or have investigated facial injuries in response to trauma mechanism. Although only few examinations exist, that pertain to the incidence of maxillofacial injuries in a general population of severely injured patients [1, 3], the data of most of the underlying investigations was collected twenty years ago and safety precautions have since significantly improved.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the existing studies on facial injuries focused on a single type of concomitant injury like brain or cervical spine [911]. Others broach the issue of concomitant injuries with a particular type of facial fracture [12, 13].…”
Section: Introductionmentioning
confidence: 99%